Pengembangan Media Pembelajaran Wayang Profesi Untuk Mengenalkan Jenis Pekerjaan Pada Siswa SD - Dede Trie Kurniawan; Auliya Aenul Hayati; Sri Maryanti (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to develop the lecture method of prospective elementary school teachers in utilizing puppet media as an implementation of local wisdom and storytelling skills in explaining the job profession to elementary school students. The use of puppets as learning media in the form of fairy tales contains subject matter that is rich in the applicative value of character education and moral values for students. Puppet shows can make learning more effective and efficient because of the elements of education such as students, educators, educational interactions, educational goals, subject matter, tools and methods and the educational environment to be fulfilled. One example of a theme in the 2013 curriculum that can use the puppet profession as an educational medium of moral value is the theme